(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2009)
The present paper is the third in the series and concludes the revision of the Pliocene naticids of northern and central Italy. It expands to 31 the total number of species and subspecies of this family recovered so far from the Pliocene deposits of the investigated area. Of the thirteen taxa covered in this study, eight (bononiensis, exturbinoides, grossularia, guillemini, helicina helicina, magenesi, notabilis and pulchella) belong to the genus Euspira Agassiz in J. Sowerby, 1837, one (olla) belongs to the genus Neverita Risso, 1826, two others (fasciolata and intricata) are members of Payraudeautia Bucquoy, Dautzenberg & Dollfus, 1883, and the last two (perregulare and striatum) belong to the genus Sinum Röding, 1798. All thirteen taxa considered in this paper are described and commented on in the systematic account. Since species herein recorded under Euspira were often assigned to Polinices Montfort, 1810 by earlier workers, both genera are discussed and their characters are defined on the basis of their respective type species. A significant output is that the tropical genus Polinices, well represented in Late Oligocene and Miocene naticid assemblages of Europe, disappeared from that area and there are no reliable records of it subsequent to the Tortonian. Also the relations between Polinices and Neverita are discussed and their respective distinguishing characters are pointed out. This study demonstrates that the taxonomic relevance of a particular character may change greatly depending on the subfamily considered, and cannot be extended to Naticidae as a whole. Naticine species are confidently identifiable primarily by characters of their opercula. These latter can be combined with protoconch characters and color patterns, umbilical callus and umbilical characters in descending order of importance. Poliniceine and sinine species are readily and univocally distinguished by a combination of protoconch and umbilical characters, the larval shell being the most important element. In the case of Neverita, Payraudeautia and Sinum species, the teleoconch shape, the aperture and the umbilical callus also may have diagnostic value. The teleoconch shape appears to have been overrated by most workers.